Tourism: A Tool for Track-two Diplomacy in Promoting People-to-People Relations Between Nepal and China - Karki, Neeru (Journal of APF Command and Staff College, 2020)
This paper is a treatise on how citizen diplomacy between Nepal and China could be leveraged by adapting tourism industry as a track two intermediary sector. Believing that the apparent insufficiencies and repudiation created during inter-governmental deliberation through track-one diplomacy could be enhanced through track-two diplomacy as an effective measure, this paper attempts to recognize the role of tourism industry in establishing alternative political channel of communication which pulls the cooperation of track one decision-making that benefits people of Nepal and China. Both nations can draw strength from the diversity that prevails irrespective of uneven size, power potential, historical complexes and different speed in the development. This paper also tries to address the gap in the academic arguments regarding the conceptualization, essence, and practicability of citizen diplomacy in foreign policy processes and explores multiple micro-level themes and actors enhancing citizen diplomacy through the tourism industry in the context of Nepal-China relationships. Based on the aforementioned scene, the researcher situates the experience as an exchange fellow student, vis-à-vis tourism and the peace-through-tourism idea and mention ways of people-to-people engagement for multiple stakeholders.